Townships for Successful People Urbanisation and Marginalisation in North Bengal. - Saswati Biswas (2013)
Urbanisation is not merely an increase in the urban population compared to the rural; it also has a very close linkage with far reaching transformations in the national and international scenario. This has come to be true for not only the developed regions of our country but also for North Bengal which for all practical purposes is considered a backward region. In neo-liberal regional policy, areas which have potential to develop as townships are selling themselves in a national and global market place of cities and townships. In North Bengal, the setting up of Uttaroyan Township in the Chandmoni tea garden is a case of urbanisation of the neo-liberal type; it was selected as a site of urban development by closing down the tea garden as nonviable. This paper attempts to show that as a „successful‟ township was being constructed the former tea garden workers were getting more and more marginalised without rehabilitation or alternate source of income.